Marine foraging ecology influences mercury bioaccumulation in deep-diving northern elephant seals - Sarah H. Peterson; Daniel P. Costa; Joshua T. Ackerman (Proceedings of the Royal Society B: Biological Sciences, 2015)
Mercury contamination of oceans is prevalent worldwide and methylmercury concentrations in the mesopelagic zone (200–1000 m) are increasing more rapidly than in surface waters. Yet mercury bioaccumulation in mesopelagic predators has been understudied. Northern elephant seals ( Mirounga angustirostris ) biannually travel thousands of kilometres to forage within coastal and open-ocean regions of the northeast Pacific Ocean. We coupled satellite telemetry, diving behaviour and stable isotopes (carbon and nitrogen) from 77 adult females, and showed that variability among individuals in foraging location, diving depth and δ 13 C values were correlated with mercury concentrations in blood and muscle. We identified three clusters of foraging strategies, and these resulted in substantially different mercury concentrations: (i) deeper-diving and offshore-foraging seals had the greatest mercury concentrations, (ii) shallower-diving and offshore-foraging seals had intermediate levels, and (iii) coastal and more northerly foraging seals had the lowest mercury concentrations. Additionally, mercury concentrations were lower at the end of the seven-month-long foraging trip ( n = 31) than after the two-month- long post-breeding trip ( n = 46). Our results indicate that foraging behaviour influences mercury exposure and mesopelagic predators foraging in the northeast Pacific Ocean may be at high risk for mercury bioaccumulation.